High shielding effect in x-band microwave frequencies of Ferrite-OPEFB-PTFE nanocomposites - Khamis, Ahmad (2022)
Ferrites are the most common materials for microwave absorbing applications that widely used to eliminate undesired or stray radiated electromagnetic signals which could interfere with a system’s operation. This project investigates using the recycled Ferrite (Fe2O3) jointly with biodegradable oil palm empty fruit bunch fiber (OPEFB) as fillers and Polytetrafluoroethylene (PTFE) as the host matrix for microwave shielding applications. Hematite (Fe2O3) fillers were recycled from the steel waste (mill scale waste) material and the particle sizes decreased to 11.3 nm after six hours of high energy ball milling. Four different batches of composites were fabricated as follows: Fe2O3-PTFE (batch 1), OPEFB-PTFE (batch 2), OPEFB-PTFE (batch 3), and Fe2O3-OPEFB-PTFE (batch 4) composites. The materials composition, complex permittivity, complex permeability, scattering parameters, density, structural, thermal, and tensile properties of prepared samples were investigated. The COMSOL software based on finite element method (FEM) was used to calculate the scattering parameters and visualize the electric field distribution in the nanocomposites. The coefficient of thermal expansion (CTE) of PTFE sample and 25%Fe2O3 (A) nanocomposite was respectively 65.28×10-6/ ᵒC and 39.84×10-6/ ᵒC, therefore, the recycled Fe2O3 nanofiller enhanced the thermal properties of the nanocomposites. The density increased from 2.2 g/cm3 to 2.54 g/cm3 when the content of Fe2O3 increased from 5 wt.% to 25 wt.% while it decreased from 2.08 g/cm3 to 1.5 g/cm3 when OPEFB increased 5 wt.% to 25 wt.%. At 10 GHz, the complex permittivity of Fe2O3-PTFE nanocomposites increased from (2.2 – j × 0.10) to (3.1 – j × 0.22), while, the complex permeability increased from (1.03 – j × 0.017) to (1.1 – j × 0.038) when the percentage of Fe2O3 increased from 5% to 25%. The transmission coefficients |S21| of the nanocomposites decreased with increasing Fe2O3 content. The |S21| values of Fe2O3-OPEFB-PTFE nanocomposites ranged from 0.84 to 0.62, while, the values of Fe2O3-PTFE nanocomposites varied from 0.86 to 0.74 at 8.2 GHz. The |S11| values of Fe2O3- OPEFB-PTFE nanocomposites ranged from 0.52 to 0.63, while, the values of Fe2O3-PTFE nanocomposites varied from 0.50 to 0.62 at 8.2 GHz. The comparison between the measured and calculated scattering parameters showed a very good agreement. In addition, the total shielding effectiveness (SE) values increased with increasing the content of Fe2O3 nanofiller. At 10 GHz, the range of total SE values for Fe2O3-PTFE nanocomposites was from 12.8 dB to 18.3 dB, while, the range of Fe2O3-OPEFB-PTFE nanocomposites was from 15.6 dB to 19.6 dB. The prepared nanocomposites can therefore be used as promising alternatives for microwave shielding applications due to their shielding effectiveness, low density, low cost, and biodegradability. The recycled Fe2O3 nanoparticles can be used as fillers in polymeric composites for microwave shielding applications due to their low cost, good thermal stability and high shielding effectiveness.